Safety Analysis Factor Of Smart Shredder Machine Frame For Face Mask Waste - Hendi Lilih Wijayanto; Amiruddin Amiruddin; Angga Tegar Setiawan; Joko Sulistyo; Yusdianto Yusdianto (Politeknik Negeri Lhokseumawe, 2024)
The COVID-19 pandemic emerged as a global public health threat. Hence, the potential danger increased the use of health masks, resulting in increased medical waste in the environment. This incident also occurred in Morowali District, especially in the PT Indonesia Morowali Industrial Park area. The waste produced by employees was disturbing; thus, it required urgent prevention and control of a pandemic. During the pandemic, the industrial area (IMIP) needed to provide various health protocol facilities that directly/indirectly benefited employees' health. This research designed a tool to solve this problem, namely the frame design of the smart shredder machine for face mask waste. This device works automatically (IOT) to shreds, process, and sterilize mask waste. The results of this tool can be monitored through periodic applications for the mask waste sterilization system and the destroyed mask waste storage system. This tool is suitable for placing in high-mobility industrial areas, such as the IMIP industrial area, which has around 60,000 employees.